Extinction Phenomenon and Decay Estimate for a Quasilinear Parabolic Equation with a Nonlinear Source - Dengming Liu; Luo Yang (Advances in Mathematical Physics)
By energy estimate approach and the method of upper and lower solutions, we give the conditions on the occurrence of the extinction and nonextinction behaviors of the solutions for a quasilinear parabolic equation with nonlinear source. Moreover, the decay estimates of the solutions are studied.